Rājyābhiṣeka paddhatiḥ = Rajyabhisheka paddhati - Ukāvyāsa (Rasaśālā Ilekṭrika Priṅtiṅga Presa, 1945)
Manual for rituals for the coronation ceremony of King; includes translation in Gujarati and English.